Exploring midwives' perception of confidence around facilitating water birth in Western Australia: A qualitative descriptive study. - Nicholls, S.; Hauck, Yvonne; Bayes, S.; Butt, J. (2015)
OBJECTIVE: the option of labouring and/or birthing immersed in warm water has become widely available throughout hospitals in the United Kingdom and Europe over the last two decades. The practice, which also occurs in New Zealand and interstate in Australia, has until recently only been available in Western Australia for women birthing at home with a small publically funded Community Midwifery Program. Despite its popularity and acceptance elsewhere, birth in water has only recently become an option for women attending some public health services in Western Australia. The Clinical Guidelines developed for the local context that support water birth require that the midwives be confident and competent to care for these women. The issue of competency can be addressed with relative ease by maternity care providers; however confidence is rather more difficult to teach, foster and attain. Clinical confidence is an integral element of clinical judgement and promotes patient safety and comfort. For this reason confident midwives are an essential requirement to support the option of water birth in Western Australia. The aim of this study was to capture midwives' perceptions of becoming and being confident in conducting water birth in addition to factors perceived to inhibit and facilitate the development of that confidence. DESIGN: a modified grounded theory methodology with thematic analysis. SETTINGS: four public maternity services offering the option of water birth in the Perth metropolitan area. PARTICIPANTS: registered midwives employed at one of the four publicly funded maternity services that offered the option of water birth between June 2011 and June 2013. Sixteen midwives were interviewed on a one to one basis. An additional 10 midwives participated in a focus group interview. FINDINGS: three main categories emerged from the data analysis: what came before the journey, becoming confident - the journey and staying confident. Each contained between three and five subcategories. Together they depicted how midwives describe the journey to becoming confident to support women who have chosen the option to water birth and how they are able to retain that confidence once achieved. IMPLICATIONS FOR PRACTICE: three key implications emerged from this study, the first was that students and graduate midwives could benefit from the opportunity to work in midwifery led maternity settings that support normal physiological child birth and that accessing such practical placements should be encouraged. Secondly, maternity services would benefit from learning opportunities directed specifically at experienced midwives addressing their particular requirements. Finally, midwives are the custodians of normal physiological birth, attendance at educational days with a focus on supporting this primary role should be mandatory, to inform midwives on current evidence found to support normal birth which includes options such as water birth.